The Diversity of Medicinal Plant Species used by the Local Communities in Kluet Utara, Aceh, Indonesia - Antika, Maulida; Suwardi, Adi Bejo; Indriaty, Indriaty (Jurnal Biologi Tropis, 2024)
Kluet Utara is an area with high biodiversity, including medicinal plant species, which have been used for generations. However, traditional knowledge regarding the use of plants as medicine is threatened by modernization. This study aims to determine the diversity of medicinal plant species and their use in medicine by the local communites in Kluet Utara sub-district, South Aceh. The study was conducted in Gunung Pudung Village and Suaq Geuringgeng Village, Kluet Utara sub-district, South Aceh district, Indonesia. Data on the use of plants as medicine were collected through interviews involving 103 randomly selected informants. A total of 69 species of medicinal plants belonging to 36 botanical families were recorded in the study areas. Curcuma longa, Zingiber officinale, Cocos nucifera,Adenostemma lavenia, Blumea balsamifera, Piper betle, Colubrina asiatica, Gardenia jasminoides, and Citrus × aurantiifolia are species commonly used by the local communities in Kluet Utara. These plants are used to treat various types of diseases, both infectious and degenerative diseases.